Pengaruh Kompetensi, Literasi Digital, Berpikir Kritis terhadap Kesiapan Kerja Siswa Kelas XII - Haniah, Nabila Rohmatul; Wirawan, Arif Wahyu (Paedagogie, 2025)
This study is motivated by the growing demand of the industrial sector for vocational high school (SMK) graduates who are work-ready, which is influenced by mastery of competencies, digital literacy, and critical thinking skills. The research aims to analyze the effect of these three variables on the work readiness of students at SMK Ma’arif Kota Magelang. A quantitative approach with an associative research design was employed, involving all 54 twelfth-grade students of the Office Management and Business Services program using a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regressio with t-test, F-test, and determination coefficient. The results indicate that individually, competence, digital literacy, and critical thinking do not have a significant effect on work readiness, while simultaneously they significantly influence work readiness with a contribution of 52.8%. These findings highlight that student work readiness is multidimensional, requiring the synergy of technical competence, digital literacy, and critical thinking. The practical implication suggests that vocational education should strengthen competency-based curricula integrated with digital learning and strategies that enhance critical thinking to produce graduates who are adaptive and competitive in the modern labor market.